Question #0ae43

1 Answer
Feb 18, 2017

∫ t sin 9t dt = 1/81 (sin(9t) - 9t * cos(9t))181(sin(9t)9tcos(9t))
Use integration by parts to solve.

Explanation:

Using integration by parts:

∫ t sin 9t dt = t*int sin(9t) dt - int(int sin(9t) dt) dttsin(9t)dt(sin(9t)dt)dt

∫ t sin 9t dt = t*(-cos(9t)/9) - int(-cos(9t)/9) dtt(cos(9t)9)(cos(9t)9)dt

∫ t sin 9t dt = -tcos(9t)/9 + sin(9t)/81 tcos(9t)9+sin(9t)81

∫ t sin 9t dt = 1/81 (sin(9t) - 9t * cos(9t))181(sin(9t)9tcos(9t))

Please ask if you need more help using integration by parts.

Rory.